The Conformal Finite-Difference Time-Domain Simulation of GPR Wave Propagation in Complex Geoelectric Structures. (24th February 2020) - Yang, Man; Fang, Hongyuan; Chen, Dazhong; Du, Xueming; Wang, Fuming
Abstract : The finite-difference time-domain (FDTD) method adopts the most popular numerical model simulating ground penetrating radar (GPR) wave propagation in an underground structure. However, a staircase approximation method is usually adopted to simulate the curved boundary of an irregular object in the FDTD and symplectic partitioned Runge-Kutta (SPRK) methods. The approximate processing of rectangular mesh parameters will result in calculation errors and virtual surface waves for irregular targets of an underground structure. In this paper, we examine transverse mode (TM) electromagnetic waves with numerical models of electromagnetic wave propagation in geoelectric structures with conformal finite-difference time-domain (CFDTD) method technology in which the effective dielectric parameters are used to accurately simulate the dielectric surface and to absorb waves at the edges of the grid. The third orders of the transmission boundary are used in this paper. Additionally, three complex geocentric models of inclined layered media, spherical media, and three-layered pavement model with structural damages are set up for simulation calculations, then we carry out the actual radar wave detection in a laboratory as the fourth numerical example. Comparison of simulated reflectance waveform of FDTD, symplectic partitioned Runge-Kutta (SPRK), and CFDTD methods shows that at least 50% of the virtual waves can be reduced by using the proposed algorithm. Wiggle diagrams of FDTD and CFDTD methods show that much of the virtual waves have been reduced, and the radar image is clearer than before. This provides a method for the detection of complex geoelectric and layered structures in actual engineering.